Oncofertility in the setting of advanced cervical cancer - A case report - Catherine Gordon; Joseph C. Carmichael; Krishnansu S. Tewari (Elsevier, 2018)
Objective: To consider fertility options in women with advanced cervical cancer. Design: Case report. Setting: Large tertiary care center. Patient: A 30-year-old nulligravida woman diagnosed with FIGO Stage IBI squamous cell carcinoma of the cervix that had metastasized to a pelvic lymph node. Interventions: Robotic radical trachelectomy with pelvic lymphadenectomy and cerclage placement, followed by ovarian stimulation with oocyte retrieval and in vitro fertilization. Subsequent therapy included adjuvant chemoradiation and embryo transfer to a surrogate mother. Main outcome measures: Cervical cancer remission, live birth from surrogate pregnancy. Results: 33-year-old woman in her third year of remission from advanced cervical cancer with healthy twin girls. Conclusions: Fertility options may exist for patients even in the setting of metastatic cervical cancer. Early involvement of a reproductive endocrinologist is imperative. This case emphasizes the importance of cross-specialty communication. Keywords: Cervical cancer, Oncofertility, Radical trachelectomy, In vitro fertilization